Climate variability and change: Farmer perceptions and understanding of intra-seasonal variability in rainfall and associated risk in semi-arid Kenya - Rao, K.P.C.; Ndegwa WG; Kizito, K.; Oyoo A (Cambridge University Press, 2011)
This study examines farmers perceptions of short- and long-term variability in climate, their ability to discern trends in climate and how the perceived trends converge with actual weather observations in five districts of Eastern Province in Kenya where the climate is semi-arid with high intra- and inter-annual variability in rainfall. Field surveys to elicit farmers perceptions about climate variability and change were conducted in Machakos, Makueni, Kitui, Mwingi and Mutomo districts. Long-term rainfall records from five meteorological stations within a 10 km radius from the survey locations were obtained from the Kenya Meteorological Department and were analysed to compare with farmers observations. Farmers responses indicate that they are well aware of the general climate in their location, its variability, the probabilistic nature of the variability and the impacts of this variability on crop production. However, their ability to synthesize the knowledge they have gained from their observations and discern long-term trends in the probabilistic distribution of seasonal conditions is more subjective, mainly due to the compounding interactions between climate and other factors such as soil fertility, soil water and land use change that determine the climate's overall influence on crop productivity. There is a general tendency among the farmers to give greater weight to negative impacts leading to higher risk perception. In relation to long-term changes in the climate, farmer observations in our study that rainfall patterns are changing corroborated well with reported perceptions from other places across the African continent but were not supported by the observed trends in rainfall data from the five study locations. The main implication of our findings is the need to be aware of and account for the risk during the development and promotion of technologies involving significant investments by smallholder farmers and exercise caution in interpreting farmers perceptions about long-term climate variability and change.